2016
DOI: 10.1016/j.bbrc.2016.07.094
|View full text |Cite
|
Sign up to set email alerts
|

Serum- and glucocorticoid-inducible kinases in microglia

Abstract: Microglia are derived from myelogenous cells and contribute to immunological and inflammatory responses in central nervous system. They play important roles not only in infectious diseases and inflammation after stroke, but also in psychiatric diseases such as schizophrenia. While recent studies suggest the significances of serum- and glucocorticoid-inducible kinases (SGKs) in other immune cells such as macrophages, T cells and dendritic cells, their role in microglia remains unknown. Here we, for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…In our studies, a strong response of the MR and GR target gene Sgk1 was found in the SHR hippocampus. Although we did not localise the cellular type responsible for the increased Sgk1 mRNA, the kinase has been detected in neurones, oligodendrocytes, astrocytes and microglia . Lang et al .…”
Section: Discussionmentioning
confidence: 59%
“…In our studies, a strong response of the MR and GR target gene Sgk1 was found in the SHR hippocampus. Although we did not localise the cellular type responsible for the increased Sgk1 mRNA, the kinase has been detected in neurones, oligodendrocytes, astrocytes and microglia . Lang et al .…”
Section: Discussionmentioning
confidence: 59%
“…As a consequence of phosphorylation of Ser507 and/or 750 residues of ULK2 by SGK1, its phosphorylation and association with AMPK1α were decreased, coupled with an increase of an antagonistic effect on its autophagy (Figure 4, Table 1). SGK1, similar to Akt kinase as a downstream effector of PI3K-PDK1 signal pathway for cell survival [13] [19], can inhibit ULK2 autophagy activity by phosphorylation as its authentic substrate proteins until they are active (Figure 4). Therefore, cell survival and autophagy are not antagonistic, but agonistic for cell survival in the transformed cell line [14] [15] [16].…”
Section: Discussionmentioning
confidence: 99%
“…For the cell amount control, the western blot with actin Ab was shown. The autophagy activity which was detected by LC3 Ab western (third lane) was 5 times enhanced by the specific SGK1 inhibitor (GSK-650394) treatment [19] than by the insulin or no treatment control. This is one of four repeated experiment results.…”
Section: Interaction Of Ulk2 With Lc3 Is Enhanced By Sgk1 Inhibitor Tmentioning
confidence: 96%
See 1 more Smart Citation
“…Blocking of SGK2 activity was assessed by inhibiting SGK2 expression using iRNA (Dharmacon Accell siRNA assay: #E-004673-00-0005, GE Healthcare, Chicago, IL) (see Fig. S2) [18] or blocking its kinase activity using the SGK-1/2 inhibitor GSK650394 (Tocris Biosciences, Bristol, UK: catalog # 3572; 2 μM) [19]. Dexamethasone (1 μM) was used as a positive control.…”
Section: Sgk Blocking Assaysmentioning
confidence: 99%